162 Coronary artery calcification on non-gated, non-cardiac ct has prognostic and treatment implications regardless of age. (6th June 2022) - Graby, John; Soto-Hernaez, Jimena; Murphy, David; Oldman, James; Burnett, Tim; Charters, Pia; Barrishi, Adam; Thanaraaj, Thuvaarahan; Masterman, Ben; Khavandi, Ali; Rodrigues, Jonathan
Abstract : Introduction: Coronary artery disease (CAD) is a progressive, inflammatory disorder with calcification forming as plaque heals. Coronary artery calcification (CAC) is thus a biomarker of CAD. The 2020 BSCI/BSTI guidelines recommended, for the first time, reporting CAC on all thoracic CT regardless of the indication and acquisition modality. However, its routine reporting is infrequent and the clinical relevance of this in all age groups has been debated. This study assessed CAC prevalence, prognosis and the potential impact of its reporting on management in unselected patients undergoing routine non-cardiac thoracic CT. Methods: A retrospective analysis of 1400 consecutive non-cardiac chest CT imaging performed in our institution from 1st January 2015 was performed until 200 individual patient scans in each age group (<40, 40–49, 50–59, 60–69, 70–79, 80–89, and ≥90) were reached. Duplicates, incomplete imaging and scans with evidence of prior coronary intervention were excluded.CTs were re-reviewed for CAC presence and severity was graded (none, mild, moderate, severe). Electronic records were reviewed for comorbidities, pre-existing CAD, statin prescription and clinical outcomes (myocardial infarction [MI], stroke and all-cause mortality). Impact on management was assessed against patient's history of statin prescription or pre-existing indications for it prior to CAC identification. Results: The final cohort was 1344 (mean age 63±20, 590 [44%] male) after excluding 9 (0.6%) with incomplete imaging and 47 (3%) with CT evidence of prior cardiac intervention. Inter- and intra-observer variability for presence of CAC was excellent (ICC 0.95 [0.90–0.97] p<0.001; ICC 0.996 [0.991–0.998] p<0.001) as was assessment of CAC severity (ICC 0.92 [0.85–0.96] p<0.001).CAC (of any degree) was present in 728/1344 (54%) of patients. CAC was present significantly more frequently in males (61% vs 49%, p<0.001) and rising age (p<0.001), and CAC severity increased significantly with age (p<0.001).Incidental CAC was present in a high proportion of patients without known CAD or dyslipidaemia who were not on a statin at the time of their scan in all age groups (range: 100% of patients <40 with CAC to 42% aged 80–89). 'Number needed to report' to impact management was 3 (all age groups), ranging from 50 if aged <40 to 2 if ≥90.691 (51%) patients had died at a median follow-up of 73 months (IQR 14–82). Presence of CAC was significantly associated with risk of MI (p<0.001), stroke (p<0.001) and a composite of all-cause mortality, MI or stroke (p<0.001), which was predicted by both CAC presence (HR 2.92 [2.48–3.43] p<0.001) and increasing CAC severity (HR 5.17 [3.89–6.86] p<0.001 for severe CAC). Conclusion: The grading of CAC presence and severity was reproducible, and although the prevalence rose with age, prognostic and treatment implications were maintained across all age groups. CAC presence and severity detected patients at increased risk of MI, stroke and all-cause mortality and identifies a significant proportion of untreated patients. Its reporting provides a simple, opportunistic approach to risk-stratify patients who may benefit from cardiovascular risk optimisation in all age groups. Conflict of Interest: nil